Boundary shear stress distribution and flow structures in trapezoidal channels - Ansari, Kamran (2011)
The commercially available Computational Fluid Dynamics (CFD) software ANSYS-CFX version 11 (2008) is employed to predict the distribution of the bed and sidewall shear stresses in trapezoidal open channels. The investigation includes computation of wall shear stress (1) directly, using CFD for a range of channels layouts (straight, turning, with ridges), and (2), building on the division line concept initially formulated by Leighly in 1932 and later by Einstein in 1942, through the evaluation of the Guo and Julien (2005) equations, as proposed by Cacqueray et al. (2009). These equations include the two complex integral terms II and III, pertaining to viscous and secondary current effects, have been analysed for each cross section, for straight channels.